THE EFFECT OF ORGANIZATIONAL CULTURE, INTERNAL AUDIT, AND WHISTLEBLOWING SYSTEM ON FRAUD PREVENTION DURING THE COVID-19 PANDEMIC AT PT DWIMANUNGGAL KARYA INDONESIA - Lainun Awanis; Dina Dwi Oktavia Rini (Magister Akuntansi, Universitas Atma Jaya Makassar, 2023)
This study aims to determine the effect of organizational culture, internal audit, and whistleblowing system on fraud prevention during the covid-19 pandemic at PT Dwimanunggal Karya Indonesia Sidoarjo. The method used in this research is quantitative method with primary data obtained from the distribution of questionnaires measured using a likert scale. This study uses a saturated sampling technique so that the entire population is used as a research sample with a total of 40 company’s employees as respondents. The analytical method used in this study is multiple linear regression analysis and the program used to analyze the data is using SPSS Statistics 26. The results show that organizational culture has no effect on fraud prevention during the covid-19 pandemic, internal audit has no effect on fraud prevention during the covid-19 pandemic, while the whistleblowing system has an effect on fraud prevention during the covid-19 pandemic.